An eight-speed rear transmission hub with a novel cam-type gear-shifting mechanism for bicycles. Issue 2 (2nd April 2016) - Wu, Yi-Chang; Chang, Che-Wei
Abstract: In this study, the conceptual design of an eight-speed rear transmission hub with a novel cam-type gear-shifting mechanism for bicycles is proposed. The main body of the transmission hub is a distributed-flow type planetary gear mechanism to provide eight forward gears. A design process for the embodiment design of a rotary-type gear-shifting mechanism is presented and illustrated. By combining the planetary gear mechanism with the gear-shifting mechanism, a novel eight-speed rear transmission hub for bicycles is generated. A 3-D printed prototype is also manufactured for further testing. Abstract :